Adaptive Techniques for Localization Analysis - Steinmann, Paul; Willam, Kaspar (Proceedings of ASME WAM'92 Symposium on Adaptive, Multilevel and Hierachical Computational Strategies, 1992)
In this paper we address the adaptive resolution of localized failure bands. To this end the theoretical framework of localization within the `classical' continuum theory is revisited and examples for the analysis of the localization tensor are presented. The prominent role of element design and orientation is demonstrated for a single element with the `Weak Localization Element Test', and at the structural level with the eigen-analysis of a flat steel bar. Next, the basic h-adaptivity strategy for capturing localization within BVP is examined. Finally, the crucial influence of mesh alignment is highlighted with two adaptive calculations of the non-uniform tension test of a flat specimen in plane stress.
UnivIS-Import:2015-04-16:Pub.1992.tech.FT.FT-TM.adapti